The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2011
DOI: 10.1111/j.1944-9720.2011.01153.x
|View full text |Cite
|
Sign up to set email alerts
|

Research on the Integrated Performance Assessment in an Early Foreign Language Learning Program

Abstract: This article reports on the implementation of the Integrated Performance Assessment (IPA) in an Early Foreign Language Learning program. The goal of this research was to examine the performance of grade 4 and 5 students of Spanish on the IPA. Performance across the three communicative tasks is described and modifications to IPA procedures based on the needs of the young learner are presented. Comparisons of the performance of monolingual and multilingual students and information collected through a student pos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
35
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 25 publications
(43 citation statements)
references
References 24 publications
8
35
0
Order By: Relevance
“…Beyond these findings, the correlational data suggest that instruction across K–12 is not consistent in the treatment of the three modes of communication, suggesting that the type of National Standards–based instruction that the profession advocates has not yet fully taken hold, particularly at the high school level. Furthermore, this study, along with the K–5 IPA study by Davin et al (), revealed an imbalance in outcomes across the three modes; that is to say that the interpretive mode, particularly when operationalized as listening comprehension, tends to have lower overall results than the other two modes. An implication for IPA‐related research is that future studies need to balance instruction to match the assessment, an issue that is addressed later in this review.…”
Section: The Communication Goalsupporting
confidence: 45%
See 1 more Smart Citation
“…Beyond these findings, the correlational data suggest that instruction across K–12 is not consistent in the treatment of the three modes of communication, suggesting that the type of National Standards–based instruction that the profession advocates has not yet fully taken hold, particularly at the high school level. Furthermore, this study, along with the K–5 IPA study by Davin et al (), revealed an imbalance in outcomes across the three modes; that is to say that the interpretive mode, particularly when operationalized as listening comprehension, tends to have lower overall results than the other two modes. An implication for IPA‐related research is that future studies need to balance instruction to match the assessment, an issue that is addressed later in this review.…”
Section: The Communication Goalsupporting
confidence: 45%
“…Although learner outcomes were not reported in this seminal article, Adair‐Hauck et al () presented the IPA as a tool with great potential for National Standards–based assessment, instruction, learning, and outcomes research across the levels of instruction. Davin, Troyan, Donato, and Hellman () demonstrated that potential at the K–5 level.…”
Section: The Communication Goalmentioning
confidence: 98%
“…In their study of a group of L2 Spanish learners in a Latin American culture and civilization class at the U.S. Air Force Academy, Glisan, Uribe, and Adair‐Hauck () examined the effectiveness of IPA, in this case on an instructional unit on illegal immigration, in providing information about the 25 participants' use of the target language in the three modes of communication. As in Davin et al's () study, the participants exhibited their lowest level of performance in the interpretive mode. However, unlike Davin et al's students, the learners performed best in the presentational mode, perhaps because many of the courses in which the students were enrolled featured this type of assessment.…”
Section: Review Of Literaturesupporting
confidence: 58%
“…Table lists the participants in each group and each student's proficiency rating. Language proficiency had been determined during the previous semester through the implementation of an Integrated Performance Assessment (Davin, Troyan, Donato, & Hellman, ).…”
Section: Contextmentioning
confidence: 99%